Antibacterial Activity Test of Karamunting Leaf Extract (Melastoma malabathricum L.) Against Eggshell Bacteria - Yutha Nadiroh Manda; Amkani Angelita Pakpahan; Hughes Bazura; Joseph Raja Oloan Sihotang; Rafli Susanto; Nurbaity Situmorang; Endang Sulistyarini Gultom (BIOPENDIX, 2026)
This study aimed to evaluate the antibacterial activity of karamunting leaf extract (Melastoma malabathricum L.) against bacteria isolated from eggshells. Eggshells are known as one of the primary contamination sources for foodborne bacteria, which can pose potential health risks to consumers. The ethanolic extract of karamunting leaves was tested using the disk diffusion method with amoxicillin as the positive control and 96% ethanol as the negative control. The inhibition zones were measured after 24 hours of incubation at 37°C. The results showed that karamunting leaf extract produced an inhibition zone of 3.35 mm, categorized as weak antibacterial activity. In contrast, the positive control, amoxicillin, generated a much larger inhibition zone of 22.89 mm, while the negative control showed no inhibition. The antibacterial effect of the extract is believed to result from the presence of bioactive secondary metabolites, including flavonoids, tannins, saponins, steroids, and phenolic compounds, which function by disrupting bacterial cell walls, altering membrane permeability, denaturing proteins, and inhibiting enzyme activity. Although the antibacterial potential of karamunting leaf extract is lower than that of synthetic antibiotics, it still demonstrates promising potential as a natural antibacterial agent that is safer and more environmentally friendly. Further studies are recommended to assess the activity at different extract concentrations and solvent fractions to achieve more optimal antibacterial effects.